2004
DOI: 10.1021/ef034004b
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Naphthenic Acids and Other Corrosivity-Related Characteristics in Crude Oil and Vacuum Gas Oils from a Mexican Refinery

Abstract: To understand the relationship between total acid number and sulfur content, relative to corrosivity, a complete characterization of these parameters along the distillation curve of a desalted crude oil was performed. Naphthenic acid identification and a complete physical and chemical characterization of crude oil, light vacuum gas oil, and heavy vacuum gas oil samples are also presented. The results found in this work show that there is a relationship between total acid number and corrosivity in the distilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 13 publications
0
16
0
2
Order By: Relevance
“…The early MS applications demonstrated that naphthenic acid distribution could be used as a fingerprint to correlate the sources of oils and source rocks. Likewise, FAB data of crude oil, light vacuum gas oil, and heavy vacuum gas oil were useful to better understand the link between naphthenic acids and the total acid number or corrosivity of refinery units (Laredo et al, 2004). The environmental importance of the MS applications was also evident at that time, as illustrated by the work of Wong et al (1996).…”
Section: A Early Historical Methodsmentioning
confidence: 99%
“…The early MS applications demonstrated that naphthenic acid distribution could be used as a fingerprint to correlate the sources of oils and source rocks. Likewise, FAB data of crude oil, light vacuum gas oil, and heavy vacuum gas oil were useful to better understand the link between naphthenic acids and the total acid number or corrosivity of refinery units (Laredo et al, 2004). The environmental importance of the MS applications was also evident at that time, as illustrated by the work of Wong et al (1996).…”
Section: A Early Historical Methodsmentioning
confidence: 99%
“…High acid crude oils (HACs) are defined as crude oils that have Total Acid Number (TAN) of more than 0.5 mg KOHg -1 oil and can go up to 8.00 mg KOHg -1 oil [1][2][3][4][5]. Total Acid Number (TAN) refers to the content of organic or inorganic acids presents in the crude oil and commonly defined as the amount of potassium hydroxide (KOH) in milligrams required to neutralize one gram of crude oil [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…[ [10][11][12] 3) el uso de solventes o soluciones para extraer la mezcla compleja de ácidos nafténicos. [13][14][15][16][17][18] Otros como: eliminación del agua en el crudo por rascado o deshidratación, uso de inhibidores de corrosión, biocidas para la prevención de la corrosión microbiana, estabilización del pH, etc.…”
Section: Introductionunclassified